In silico structural insights into a glucanase from Clostridium perfringens and prediction of structural stability improvement through hydrophobic interaction network and aromatic interaction - Nezhad, Nima Ghahremani; Eskandari, Azadeh; Omotayo, Oluwaloni Folusho; Albayati, Samah Hashim; Buhari, Sunusi Bataiya; Leow, Thean Chor (Springer, 2026)
Glucanases are widely applied in industrial applications such as brewing, biomass conversion, food, and animal feed. Glucanases catalyze the hydrolysis of glucan to produce the sugar hemiacetal through hydrolytic cleavage of glycosidic bonds. Current study aimed to investigate structural insights of a glucanase from Clostridium perfringens through blind molecular docking, site-specific molecular docking, molecular dynamics (MD) simulation, and binding energy calculation. Furthermore, we aimed to enhance structural stabilization through formation of hydrophobic interaction network. The molecular docking results illustrated that residues Glu222 and Asp187 may act as nucleophile acid/base catalyst. Moreover, the MM/PBSA results illustrated a high binding affinity of 108.71 ± 8.5 kJ/mol between glucanase and barely glucan during 100 ns simulation. The RMSF analysis illustrated a high flexible surface loop with the highest mobility at position D130. Therefore, the structural engineering was carried out through introducing a double-mutant S125Y/D130P, and the structural stability was improved by forming the hydrophobic interaction network and one π–π aromatic interaction. The spatial distance between the mutation sites and the catalytic pocket attenuates their direct impact on binding interactions within the catalytic pocket.